2021
DOI: 10.1038/s41589-020-00717-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for non-radical catalysis by TsrM, a radical SAM methylase

Abstract: TsrM methylates C2 of the indole ring of L-tryptophan (Trp) during the biosynthesis of the quinaldic acid moiety of thiostrepton. It is annotated as a cobalamin-dependent radical S -adenosylmethionine (SAM) methylase; however, TsrM does not reductively cleave SAM to the universal 5ʹ-deoxyadenosyl 5ʹ-radical intermediate, a hallmark of radical-SAM (RS) enzymes. Herein, we report structures of TsrM from Kitasatospora setae , the first of a cobalamin-dependent radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
114
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(126 citation statements)
references
References 47 publications
12
114
0
Order By: Relevance
“…Interestingly, despite low sequence identity (~29%) between CysS and TokK or ThnK, all three proteins are located within the same node of a sequence similarity network (SSN) composed of uses cobalamin in an unknown fashion to catalyze a complex ring contraction of 2'deoxyadenosine monophosphate (dAMP) (Figure S3) (14). TsrM methylates an sp 2 -hybridized carbon, C2, of L-tryptophan (Trp) by a polar mechanism (Figure S3) (11). TsrM is distinctive among all RS enzymes because it does not catalyze the formation of 5'-dA• during catalysis (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, despite low sequence identity (~29%) between CysS and TokK or ThnK, all three proteins are located within the same node of a sequence similarity network (SSN) composed of uses cobalamin in an unknown fashion to catalyze a complex ring contraction of 2'deoxyadenosine monophosphate (dAMP) (Figure S3) (14). TsrM methylates an sp 2 -hybridized carbon, C2, of L-tryptophan (Trp) by a polar mechanism (Figure S3) (11). TsrM is distinctive among all RS enzymes because it does not catalyze the formation of 5'-dA• during catalysis (11).…”
mentioning
confidence: 99%
“…TsrM methylates an sp 2 -hybridized carbon, C2, of L-tryptophan (Trp) by a polar mechanism (Figure S3) (11). TsrM is distinctive among all RS enzymes because it does not catalyze the formation of 5'-dA• during catalysis (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Co-expression of cellular machinery for Fe/S-cluster assembly along with careful handling under anoxic conditions can secure the canonical [4Fe-4S] cluster. The incorporation and instability of methylcobalamin (MeCbl), on the other hand, has proven more problematic, and recently emerged as the primary impediment to structural characterization of a true reactant complex for tryptophan 2C methyltransferase (TsrM), annotated as a rSAM enzyme [ 12 ]. TsrM catalyzes the methylation of L-tryptophan (Trp) at the C2 position during the biosynthesis of the macrocyclic peptide antibiotic thiostrepton A ( Figure 1 B) [ 13 ].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Experimental structure elucidation of the TsrM•Trp complex depicts an awkwardly oriented substrate molecule, the C2 position of which is too distant (7 Å) for methyl transfer from the cobalt ion ( Figure 1 C). To account for this inconsistency, the authors suggest that the observed binding mode is likely due to degradation of the MeCbl cofactor to aquocobalamin during crystallization and/or data collection [ 12 ]. They utilized the Glide docking program from the Schrödinger software suite to test this hypothesis following manual replacement of the observed cofactor by MeCbl ( Table 1 ) [ 14 ].…”
Section: Molecular Dockingmentioning
confidence: 99%